Determinants of Tourist Satisfaction at Lake Toba Destination: Landscape Beauty, Local Atmosphere, and Memorable Experiences - Muhammad Habib Auliya; Ruben Situmorang; Micky Tanoto; Kuandi Chandra; Roseline (Sean Institute, 2026)
This study was conducted to examine the factors influencing tourist satisfaction at the Lake Toba Destination, including landscape beauty, local atmosphere, and memorable experiences. A quantitative approach with an associative research design was employed. The study population consisted of tourists visiting the Lake Toba Priority Tourism Destination area. The sample was determined using the accidental sampling technique and the Slovin formula, resulting in 100 respondents. Data were collected through the distribution of Likert-scale questionnaires, while data analysis included classical assumption tests, multiple linear regression analysis, partial tests, simultaneous tests, and the coefficient of determination. The results revealed that landscape beauty and local atmosphere each have a positive and significant effect on tourist satisfaction. Memorable experiences were identified as the most dominant variable contributing to increased tourist satisfaction. Simultaneously, the three variables significantly influenced tourist satisfaction, with an R Square value of 0.604. These findings indicate that tourist satisfaction at Lake Toba is shaped by the integration of natural attractions, the destination’s atmosphere, and meaningful travel experiences. The study highlights the importance of experience-oriented destination management through landscape enhancement, strengthening local cultural identity, improving service quality, and developing tourism activities that create lasting impressions and encourage repeat visits.